Safety in Malaysian construction: The challenges and initiatives - Mohd Khairolden, Ghani; Zuhairi, Abd. Hamid, Dr.; Maria Zura, Mohd. Zain; Ahmad Hazim, Abdul Rahim; Kamarul Anuar, Mohamad Kamar; Muhammed Asraff, Abdul Rahman (The Institution of Engineers, Malaysia, 2011)
http://www.myiem.org.my/content/iem_bulletin_2008-183.aspx